Lecture19

# Lecture19 - Naive Gauss Elimination Begin with a11 x1 a12 x...

This preview shows pages 1–10. Sign up to view the full content.

Naive Gauss Elimination Begin with Multiply the first equation by a 21 / a 11 and subtract from second equation n n nn 2 2 n 1 1 n 2 n n 2 2 22 1 21 1 n n 1 2 12 1 11 b x a ... x a x a b x a ... x a x a b x a ... x a x a = + + + = + + + = + + + n n nn 2 2 n 1 1 n 1 11 21 2 n n 1 11 21 n 2 2 12 11 21 22 1 1 n n 2 12 1 11 b x a ... x a x a b a a b x a a a a ... x a a a a x b x a ... x a x a = + + + - = - + + - + = + + +

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
Gauss Elimination Reduce to Repeat the forward elimination to get n n nn 2 2 n 1 1 n 2 n n 2 2 22 1 n n 1 2 12 1 11 b x a ... x a x a b x a ... x a b x a ... x a x a = + + + = + + = + + + n n nn 2 2 n 2 n n 2 2 22 1 n n 1 2 12 1 11 b x a ... x a b x a ... x a b x a ... x a x a = + + = + + = + + +
Gauss Elimination First equation is pivot equation a 11 is pivot element Now multiply second equation by a ' 32 / a 22 and subtract from third equation - = - + + - = + + + = + + + + 2 22 32 3 n n 2 22 32 n 3 3 23 22 32 33 2 n n 2 3 23 2 22 1 n n 1 3 13 2 12 1 11 b a a b x a a a a x a a a a b x a x a x a b x a x a x a x a

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
Gauss Elimination Repeat the elimination of a i2 and get Continue and get n n nn 3 3 n 3 n n 3 3 33 2 n n 2 3 23 2 22 1 n n 1 3 13 2 12 1 11 b x a x a b x a x a b x a x a x a b x a x a x a x a = + + = + + = + + + = + + + + ) ( ) ( 1 n n n 1 n nn 3 n n 3 3 33 2 n n 2 3 23 2 22 1 n n 1 3 13 2 12 1 11 b x a b x a x a b x a x a x a b x a x a x a x a - - = = + + = + + + = + + + +
Now we can perform back substitution to get { x } By simple division ) ( ) ( , ) ( , 2 n 1 n n 2 n n 1 n 1 n 2 n 1 n 1 n b x a x a - - - - - - - - = + Back Substitution ) ( ) ( 1 n nn 1 n n n a b x - - =

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
Back Substitution a x a b x a b x 1 i ii n 1 i j j 1 i ij 1 i i i 1 n nn 1 n n n ) ( ) ( ) ( ) ( ) ( - + = - - - - - = = for i = n - 1, n 2, …, 1 0 a 1 i ii - ) ( Naive Gauss Elimination
Elimination of first column ) ( ) ( ) ( ) ( ) ( ) ( 1 f 4 1 f 3 1 f 2 b a a a 0 b a a a 0 b a a a 0 b a a a a 41 31 21 4 44 43 42 3 34 33 32 2 24 23 22 1 14 13 12 11 × - × - × - 11 41 41 11 31 31 11 21 21 4 44 43 42 41 3 34 33 32 31 2 24 23 22 21 1 14 13 12 11 a a f a a f a a f b a a a a b a a a a b a a a a b a a a a / / / = = =

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
Elimination of second column ) ( ) ( ) ( ) ( / / 2 f 4 2 f 3 b a a 0 0 b a a 0 0 b a a a 0 b a a a a a a f a a f b a a a 0 b a a a 0 b a a a 0 b a a a a 42 32 4 44 43 3 34 33 2 24 23 22 1 14 13 12 11 22 42 42 22 32 32 4 44 43 42 3 34 33 32 2 24 23 22 1 14 13 12 11 × - × - = =
Elimination of third column Upper triangular matrix ) ( ) ( / 3 f 4 b a 0 0 0 b a a 0 0 b a

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

## This note was uploaded on 09/05/2011 for the course EGM 3344 taught by Professor Raphaelhaftka during the Spring '09 term at University of Florida.

### Page1 / 36

Lecture19 - Naive Gauss Elimination Begin with a11 x1 a12 x...

This preview shows document pages 1 - 10. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online